(untitled) (Western European Journal of Medicine and Medical Science, 2025)
The climate analog method, developed by G. Mayer in 1909, is based on studying historical climate conditions to predict future weather patterns. This paper analyzes the theoretical foundations of the climate analog method, its role in modern climate models, and the potential for integration with artificial intelligence and big data processing technologies. Additionally, the application of this method in agriculture, water resource management, and extreme weather event forecasting is discussed.